Managerial Agency and Bond Covenants - Chava, Sudheer; Kumar, Praveen; Warga, Arthur (Review of Financial Studies, 2010)
[Based on an analysis of the agency risk for bondholders from managerial entrenchment and fraud, we derive and test refutable hypotheses about the influence of managerial agency risk on bond covenants, using a comprehensive database of corporate bonds from the 1993-2007 period. Managerial entrenchment and the risk of managerial fraud significantly influence the use of covenants, in the direction predicted by the agencytheoretic framework. Our analysis highlights the varied effects of entrenchment on different types of agency risks faced by bondholders: Entrenched managers aggravate investment risk, but ameliorate risk from shareholder opportunism. Covenant use also responds efficiently to the quality of information available regarding the risk of managerial fraud.]